Identification of Bioactive Compounds of Seaweed Sargassum sp. and Eucheuma cottonii Doty as a Raw Sunscreen Cream: Bioactive Compounds of Seaweed as a Raw Sunscreen Cream - Nurjanah; Nurilmala, Mala; Anwar, Effionora; Luthfiyana, Novi; Hidayat, Taufik (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
This study aimed at determining proximate value, vitamin E, antioxidant activity and active components extracts of Sargassum sp. and Eucheuma cottonii Doty. Extraction was done by maceration stratified method. The yield of Sargassum sp. used solvent n-hexane, ethyl acetate and methanol and amounted to 0.027 3 %, 0.133 3 %, 7.332 8 %. The yield of E. cottonii used solvent n-hexane, ethyl acetate and methanol and amounted to 0.025 7 %, 0.078 8 %, 6.758 6 %. Proximate value of Sargassum sp. is a row of moisture, ash, fat, protein and crude fiber that amounted to 82.26 %, 5.09 %, 1.26 %, 0.41 %, 0.43 %, respectively, and E. cottonii amounted to 77.27 %, 5.84 %, 2.39 %, 0.12 % and 0.67 %, respectively. Vitamin E value of Sargassum sp. was 165.19 μg mL–1 while vitamin E value of E. cottonii amounts to 160.01 μg mL–1, using HPLC method. The antioxidant activity of Sargassum sp. and E. cottonii from the methanol extract were 57.050 μg mL–1 and 105.040 μg mL–1. The active components of Sargassum sp. and E. cottonii contained in the methanol extract were flavonoids, phenols hydroquinone and triterpenoids.